2012
DOI: 10.1371/journal.pone.0049666
|View full text |Cite
|
Sign up to set email alerts
|

Human Neutral Genetic Variation and Forensic STR Data

Abstract: The forensic genetics field is generating extensive population data on polymorphism of short tandem repeats (STR) markers in globally distributed samples. In this study we explored and quantified the informative power of these datasets to address issues related to human evolution and diversity, by using two online resources: an allele frequency dataset representing 141 populations summing up to almost 26 thousand individuals; a genotype dataset consisting of 42 populations and more than 11 thousand individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 56 publications
8
39
0
2
Order By: Relevance
“…The overall Fst among the 41 location samples was 0.0022, a value which reveals the inability of forensic STRs to summarize differentiation into Fst, due to the large number of alleles, many of which with low frequencies [32], inflated intra-population variances [6, 7], and the mathematical constraint on the index [8]. Nevertheless, the departure of our value from the null (P<1E-4), showed that the sampling scheme may have the power to detect some kind of structuring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall Fst among the 41 location samples was 0.0022, a value which reveals the inability of forensic STRs to summarize differentiation into Fst, due to the large number of alleles, many of which with low frequencies [32], inflated intra-population variances [6, 7], and the mathematical constraint on the index [8]. Nevertheless, the departure of our value from the null (P<1E-4), showed that the sampling scheme may have the power to detect some kind of structuring.…”
Section: Resultsmentioning
confidence: 99%
“…Rowold and Herrera [5] used five forensic STRs and obtained phylogenetic relationships of worldwide populations consistent with other markers. Silva et al [6] detected a progressive reduction of diversity with increasing distance from Eastern Africa, a signature of the serial founder effect which accompanied the spread of modern humans out of Africa and beyond. However, these latter authors found low fixation indices, and suggested that, as far as these markers have been specifically selected to maximize the within-population (or between-subjects) variance, they carry a tiny proportion of information useful for between-population inferences.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we observed random spatial patterns of relatedness among individuals, which may indicate no restriction in gene flow across a few kilometers (see also Smouse and Peakall 1999;Peakall et al 2003;Chybicki 2017). Third, the population structure, as inferred from STRU CTU RE, was only partially consistent with geography, nevertheless STRU CTU RE clustering may be biased due to a low number of loci analyzed (Silva et al 2012). The observed departures from Hardy-Weinberg equilibrium could thus be rather attributed to substantial inbreeding (F i null avg .…”
Section: Quality Data Evaluationmentioning
confidence: 91%
“…They are quite able to detect strong genetic structure, as we have observed here with the clear differentiation between Sub-Saharan African, East Asian and European populations, for instance. However, in comparison to panels of STRs generated specifically to study diversity of human populations, forensic STRs underestimate levels of structure, thus providing lower differentiations among populations (Silva et al, 2012).…”
Section: Diversity Inmentioning
confidence: 99%
“…Previous studies have provided important contributions to understand the genetic structure of North African populations, using various genetic markers, such as mitochondrial DNA (mtDNA) (Fadhlaoui-Zid et al, 2004;Frigi et al, 2006aFrigi et al, , 2010Coudray et al, 2009;Ottoni et al, 2010;Bekada et al, 2015), Y chromosome Short Tandem Repeats (STRs) (Fadhlaoui-Zid et al, 2011, 2013Frigi et al, 2006b;Arredi et al, 2004;Bekada et al, 2015), Single Nucleotide Polymorphisms (SNP), (Henn et al, 2012, Botigué et al, 2013Haber et al, 2013), Alu insertions (Gonzalez-Pérez et al, 2003;Ennafaa et al, 2006;Frigi et al, 2011) and autosomal STRs (Bosch et al, 2001;Cherni et al, 2005a;Coudray et al, 2007aCoudray et al, , 2007bCoudray et al, , 2007cElOssmani et al, 2007ElOssmani et al, , 2009ElOssmani et al, , 2010Khodjet-El-Khil et al, 2008, 2012Gaibar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%